COMPACT DARKROOM IN THE EXPLORATION OF PHOTOGRAPHY AS AN EFFORT TO IMPROVE THE CREATIVE INDUSTRY - Anin Astiti; Tohari Caturiyanto, Setyo; Wahyudi, Johan Ies; Waskito, Setyo Bagus (Acintya, 2024)
Using a darkroom to create photogram works often gives rise to findings related to the effectiveness and efficiency of using light in the enlarger in the darkroom as well as findings to deal with problems that exist when in the darkroom. This then inspired the desire to carry out an experiment that would be useful when researchers carried out the photogram technique, but could be done outside the dark room. Through this research, it is hoped that the aim will be to obtain a solution to the problems that the researcher stated in the previous paragraph. In this applied research efforts are made to apply the research results which can be used to develop creative photography experiments, especially the photogram technique. The darkroom is an important space that must exist in the analog era. A dark room is a room that is literally dark with several devices such as enlargers and chemicals that are used for the image development process. The darkroom or darkroom is a manifestation of the development of the camera obscura in the 18th century. Portable darkrooms became very popular among artists/photographers because of their practicality in being able to travel with them, or dark-room wagons which were usually attached to a horse-drawn carriage or stroller. It is hoped that this research can provide a useful solution in terms of ease and practicality in carrying out photogram techniques so that the illumination process can be carried out outdoors (not in a dark room) so that it has more value as when using a conventional camera.